Suppression of Kv3.3 channels by antisense oligonucleotides reverses biochemical effects and motor impairment in spinocerebellar ataxia type 13 mice. Issue 12 (25th November 2021) - Zhang, Yalan; Quraishi, Imran H.; McClure, Heather; Williams, Luis A.; Cheng, YungChih; Kale, Siddharth; Dempsey, Graham T.; Agrawal, Sudhir; Gerber, David J.; McManus, Owen B.; Kaczmarek, Leonard K.
Abstract: Mutations in KCNC3, the gene that encodes the Kv3.3 voltage dependent potassium channel, cause Spinocerebellar Ataxia type 13 (SCA13), a disease associated with disrupted motor behaviors, progressive cerebellar degeneration, and abnormal auditory processing. The Kv3.3 channel directly binds Hax‐1, a cell survival protein. A disease‐causing mutation, Kv3.3‐G592R, causes overstimulation of Tank Binding Kinase 1 (Tbk1) in the cerebellum, resulting in the degradation of Hax‐1 by promoting its trafficking into multivesicular bodies and then to lysosomes. We have now tested the effects of antisense oligonucleotides (ASOs) directed against the Kv3.3 channel on both wild type mice and those bearing the Kv3.3‐G592R‐encoding mutation. Intracerebroventricular infusion of the Kcnc3 ‐specific ASO suppressed both mRNA and protein levels of the Kv3.3 channel. In wild‐type animals, this produced no change in levels of activated Tbk1, Hax‐1 or Cd63, a tetraspanin marker for late endosomes/multivesicular bodies. In contrast, in mice homozygous for the Kv3.3‐G592R‐encoding mutation, the same ASO reduced Tbk1 activation and levels of Cd63, while restoring the expression of Hax‐1 in the cerebellum. The motor behavior of the mice was tested using a rotarod assay. Surprisingly, the active ASO had no effects on the motor behavior of wild type mice but restored the behavior of the mutant mice to those of age‐matched wild type animals. Our findings indicate that, in mature intact animals, suppression of Kv3.3 expression can reverse the deleterious effects of a SCA13 mutation while having little effect on wild type animals. Thus, targeting Kv3.3 expression may prove a viable therapeutic approach for SCA13.